Comparing TIP to Wage Subsidies - Nichols, Donald A. (American Economic Review, 2016)
This paper derives some analytic results concerning the possible effects of a tax-based incomes policy (TIP), and compares them to the effects of a wage subsidy or a decreased payroll tax. The policies are compared using a model of firm equilibrium which is somewhat simpler than that of Yehuda Kotowitz and Richard Portes, and R. W. Latham and David Peel. Because the model is one of firm equilibrium, it ignores both interactions among firms and workers, and the bargaining process. As a result, it cannot answer all possible questions about the effectiveness of a TIP. Nevertheless, the model can address an important question that lies at the very heart of the issue of the possible effectiveness of a TIP: in what way would a TIP influence a firm to change its wage and price decisions, assuming nothing else in the economy were to be changed. If, as shown below, certain versions of TIP